(untitled) (Analysis in Theory and Applications, 2016)
Suppose T^k,1 and T^k,2 are singular integrals with variable kernels and mixed homogeneity or ± I (the identity operator). Denote the Toeplitz type operator byalign*T^b=_k=1^QT^k,1M^bT^k,2, align* where M^bf=bf. In this paper, the boundedness of T^b on weighted Morrey space are obtained when b belongs to the weighted Lipschitz function space and weighted BMO function space, respectively.